(3efgGL GdOcGf hOSJhQ GdCYjGfs - (3CHh Gdefj OGhO CHj fUQ Gdchgjf GdYWGQ GdESQGFjdj GdgGQhfj, Gdchgjf GdYWGQs ((3HdOI GdbSWfWjfjI s)
(3ChdgG (B:s
(3gPG efgGL GdOcGf hOSJhQ GdCYjGf ajeG jfHZi Cf jMJhi Ydjg ef GdCTQHI hGdeYGLjf hGdLhGQTfGJ hGdQHhHGJ s
(3BNQgG (B:s
(3CeG GdaVdGJ jfHZi dgG Cf jfOaY ajefYg Chd aChd MaXG ddbhI heYhfI dOaY GdaVdGJ s
(3GdfSNI HgG MhGTs
(3HBNQg hChdg ahGFO heLQjGJ WHjI ai (B5 (3ChQGbs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda (B: (3fbdJ Yf CHj GSMGbs
Keywords: (3eJaQbGJs